Factors associated with all-cause mortality and morbidity of motorcycle crash-related neurological and musculoskeletal injuries in Uganda: the MOTOR cluster randomised trial ancillary study - Lule, Herman; Mugerwa, Micheal; Abio, Anne; Oguttu, Benson; Kakeeto, Andrew; Asiimwe, Daniel; Lekuya, Hervé Monka Monka; Ssebuufu, Robinson; Kyamanywa, Patrick; Bärnighausen, Till; L Wilson, Michael; Posti, Jussi P (BMJ Publishing Group Ltd, 2025)
This study examined the factors linked to all-cause mortality and morbidity from neurological and musculoskeletal injuries during motorcycle accidents in Uganda.INTRODUCTIONThis study examined the factors linked to all-cause mortality and morbidity from neurological and musculoskeletal injuries during motorcycle accidents in Uganda.The study was part of a two-armed, parallel, multi-period, cluster-randomised controlled trial of 1003 motorcycle crash victims. Morbidity was assessed using various scoring systems, and mixed effects regression models were employed for analysis.METHODSThe study was part of a two-armed, parallel, multi-period, cluster-randomised controlled trial of 1003 motorcycle crash victims. Morbidity was assessed using various scoring systems, and mixed effects regression models were employed for analysis.Ninety-day all-cause mortality was 9.2% (82/887). Factors associated with mortality included referral-to-dispatch >1 hour (OR 4.215 (1.802-9.858), p=0.001), Kampala Trauma Score (KTS) ≤6 (OR 7.696 (1.932-30.653), p=0.004), GCS 9-12 (OR 3.432 (1.194-9.870), p=0.022), GCS ≤8 (OR 6.919 (2.212-21.645), p=0.001), intra-axial lesions (OR 78.647 (9.871-626.587), p<0.001), extra-axial lesions (OR 11.933 (1.386-102.750), p=0.024), skull fracture (OR 11.366, (1.197-107.977), p=0.034) and craniotomy (OR 0.260 (0.095-0.706), p=0.008).A percentage of 14.5% had unfavourable Glasgow Outcome Scale (1-3); associated factors included increasing age (OR 1.02 (1.013-1.045, p<.001), multiple injuries (OR 4.559 (1.185-17.531), p=0.027), KTS 7-8 (OR 2.755 (1.285-5.906), p=0.009), KTS ≤6 (OR 7.551 (2.815-20.255), p=0.001), GCS 9-12 (OR 4.07 (1.901-8.719), p=0.001), GCS ≤8 (OR 13.779 (5.643-33.645), p<0.001) and craniotomy (OR 0.149 (0.075-0.295), p<0.001).Factors associated with unfavourable patient-reported musculoskeletal outcomes included being married (OR 1.984 (1.322-2.976), p=0.001), multiple injuries (OR 1.762 (1.001-3.100), p=0.049) and enrolment after the onset of the COVID-19 pandemic (OR 2.095 (1.199-3.659), p=0.009].RESULTSNinety-day all-cause mortality was 9.2% (82/887). Factors associated with mortality included referral-to-dispatch >1 hour (OR 4.215 (1.802-9.858), p=0.001), Kampala Trauma Score (KTS) ≤6 (OR 7.696 (1.932-30.653), p=0.004), GCS 9-12 (OR 3.432 (1.194-9.870), p=0.022), GCS ≤8 (OR 6.919 (2.212-21.645), p=0.001), intra-axial lesions (OR 78.647 (9.871-626.587), p<0.001), extra-axial lesions (OR 11.933 (1.386-102.750), p=0.024), skull fracture (OR 11.366, (1.197-107.977), p=0.034) and craniotomy (OR 0.260 (0.095-0.706), p=0.008).A percentage of 14.5% had unfavourable Glasgow Outcome Scale (1-3); associated factors included increasing age (OR 1.02 (1.013-1.045, p<.001), multiple injuries (OR 4.559 (1.185-17.531), p=0.027), KTS 7-8 (OR 2.755 (1.285-5.906), p=0.009), KTS ≤6 (OR 7.551 (2.815-20.255), p=0.001), GCS 9-12 (OR 4.07 (1.901-8.719), p=0.001), GCS ≤8 (OR 13.779 (5.643-33.645), p<0.001) and craniotomy (OR 0.149 (0.075-0.295), p<0.001).Factors associated with unfavourable patient-reported musculoskeletal outcomes included being married (OR 1.984 (1.322-2.976), p=0.001), multiple injuries (OR 1.762 (1.001-3.100), p=0.049) and enrolment after the onset of the COVID-19 pandemic (OR 2.095 (1.199-3.659), p=0.009].The key determinants of mortality and adverse neurological and musculoskeletal injury outcomes observed in this study are essential for establishing core outcome sets in future research and predictive models.CONCLUSIONSThe key determinants of mortality and adverse neurological and musculoskeletal injury outcomes observed in this study are essential for establishing core outcome sets in future research and predictive models.Pan African Clinical Trial Registry (PACTR202308851460352).TRIAL REGISTRATION NUMBERPan African Clinical Trial Registry (PACTR202308851460352). MEDLINE - Academic